2005
DOI: 10.4319/lom.2005.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Development of a hyperbaric trap-respirometer for the capture and maintenance of live deep-sea organisms

Abstract: A major obstacle to the investigation of deep-sea biology is the lack of instrumentation to retrieve deep-sea organisms from their habitat alive, particularly fishes with physoclistous swimbladders. To perform physiological experiments on deep-sea fishes under in situ but controlled conditions, we constructed a high-pressure fish trap-respirometer to capture deep-water fishes at depth and return them to the surface alive at in situ pressure and temperature. Pumps and instrumentation connected aboard ship or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…comm.). In other systems with Optodes, such as bottomlanders, neither Drazen et al (2005) nor Sommer et al (2008) reported any significant Optode drift over more than 9 h. Signs of system drift of other sensors during the first 10 h can, however, be seen in control samples, although drift rates were not estimated or discussed by the authors (Griffith 1988;Briand et al 2004). …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…comm.). In other systems with Optodes, such as bottomlanders, neither Drazen et al (2005) nor Sommer et al (2008) reported any significant Optode drift over more than 9 h. Signs of system drift of other sensors during the first 10 h can, however, be seen in control samples, although drift rates were not estimated or discussed by the authors (Griffith 1988;Briand et al 2004). …”
Section: Discussionmentioning
confidence: 81%
“…The same system was used to estimate copepod respiration in small glass vessels (Koster et al 2008). Drazen et al (2005) presented a novel technique with an Optode to measure respiration rates of deep sea fish, and Sommer et al (2008) described an automatic system to regulate oxygen levels and measure sedimentwater fluxes during in situ sediment incubation at vent sites. Additionally, Pakhomova et al (2007), Almroth et al (2009), and Almroth-Rosell et al (2012) used the same type of Optodes with autonomous landers to perform sediment-water incubation studies.…”
mentioning
confidence: 99%
“…The state of our knowledge remains technology and resource limited, but steady advances (Childress et al 1978;Childress 1985;Robison 2000;Koyama et al 2002;Drazen et al 2005) have allowed the live capture, surface maintenance and measurement of a surprisingly large number of deep-sea animals. A necessarily smaller number of oxygen consumption measurements have been made in situ on the deep-sea floor but techniques for these types of investigations have also seen many advances in recent years (Smith 1978;Smith & Baldwin 1997;Priede & Bagley 2000;Bailey et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…What are the natural metabolic rates of active deepsea fishes, and how will they respond to changing CO 2 and O 2 levels? To address this question, MBARI scientists and engineers fabricated a hyperbaric fish trap ( Figure 4) capable of capturing deep-sea fishes (to 4,000 m) and returning them to the laboratory for physiological studies under the pressure, oxygen, and temperature conditions of their capture depth (Drazen et al, 2005).…”
Section: In Situ Respirometersmentioning
confidence: 99%